2010
DOI: 10.1097/mjt.0b013e3181c6c0f9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy and Tolerability of Gliclazide and Metformin Combination: A Multicentric Study in Patients With Type 2 Diabetes Mellitus Uncontrolled on Monotherapy With Sulfonylurea or Metformin

Abstract: The objective of this study was to compare the effects of gliclazide/metformin on glycemic control in patients with Type 2 diabetes mellitus uncontrolled on monotherapy with sulfonylurea or metformin. This was a prospective, open-labeled, multicentric study over 12 weeks. Patients who were diagnosed of Type 2 diabetes and were uncontrolled on monotherapy with oral hypoglycemic agents, including gliclazide and metformin, characterized by HbA1c 7% or greater and 10% or less and fasting plasma glucose (FPG) 140 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
2
16
0
6
Order By: Relevance
“…This coincides with a study conducted by Charpentier et al, Wang et al, and Pareek et al, [13][14][15] who showed a significant reduction in FBS and PPBS (P < 0.001) from baseline than either glimepiride or metformin alone. The results of the present study coincide with these studies where FBS and PPBS decreased significantly (P < 0.01) from baseline to 12 weeks (P < 0.001).…”
Section: Discussionsupporting
confidence: 71%
“…This coincides with a study conducted by Charpentier et al, Wang et al, and Pareek et al, [13][14][15] who showed a significant reduction in FBS and PPBS (P < 0.001) from baseline than either glimepiride or metformin alone. The results of the present study coincide with these studies where FBS and PPBS decreased significantly (P < 0.01) from baseline to 12 weeks (P < 0.001).…”
Section: Discussionsupporting
confidence: 71%
“…Эффективность комбинации глимепирида и метформина была доказана в исследовании с участием пациентов с СД2 без адекватного контроля на фоне монотерапии метформи-ном. Двенадцатинедельная терапия продемонстрировала эффективность комбинации в плане улучшения (сниже- [11].…”
Section: Discussionunclassified
“…According to current recommendations of the European Association for the Study of Diabetes (EASD), the American Diabetes Association (ADA), and the PTD, metformin is the first drug of choice in all patients with newly diagnosed type 2 diabetes (after exclusion of contraindications). An important advantage of metformin treatment is low risk of hypoglycaemia, at the level of the placebo [20]. Among other oral antidiabetic agents with a good safety profile, it is worth mentioning acarbose -an inhibitor of intestinal alpha-glucosidase (alone does not cause hypoglycaemia) [21], gliflozins -inhibitors of type 2 sodium-glucose cotransporter (SGLT2) [22], and inhibitors of dipeptidyl peptidase (DPP-4) [23].…”
Section: Discussionmentioning
confidence: 99%